2015
DOI: 10.1177/0163443715608259
|View full text |Cite
|
Sign up to set email alerts
|

Managing collective trauma on social media: the role of Twitter after the 2011 Norway attacks

Abstract: This study analyses the meaning-making discourse on Twitter in the 6 days following the 2011 Norway attacks. The attacks in Oslo and on the island of Utøya resulted in 77 deaths, of which 69 were youths on Utøya, where a summer camp arranged by the Norwegian Social Democratic youth organisation Arbeidernes Ungdomsfylking (AUF) was being held. The main discursive themes in the material were found to be focused on the Norwegian nation, expressions of solidarity, the meaning and outcomes of the attacks, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
4
53
0
Order By: Relevance
“…Prior research investigated Twitter communication during different human-made crisis events from the sense-making perspective. Oh et al (2012;2015), for instance, found that communication via Twitter during the so-called "January 25 Revolution" in Egypt in 2011 was structured around and quickly became dominated by a small number of hashtags and concluded that the use of hashtags contributed significantly to collective sense-making. Stieglitz et al (2018) Additionally, Eriksson (2015) showed that people used Twitter for coping and meaning-making at the collective level after the 2011 terrorist attack in Norway.…”
Section: Social Networking Sites Twitter and Sense-makingmentioning
confidence: 99%
“…Prior research investigated Twitter communication during different human-made crisis events from the sense-making perspective. Oh et al (2012;2015), for instance, found that communication via Twitter during the so-called "January 25 Revolution" in Egypt in 2011 was structured around and quickly became dominated by a small number of hashtags and concluded that the use of hashtags contributed significantly to collective sense-making. Stieglitz et al (2018) Additionally, Eriksson (2015) showed that people used Twitter for coping and meaning-making at the collective level after the 2011 terrorist attack in Norway.…”
Section: Social Networking Sites Twitter and Sense-makingmentioning
confidence: 99%
“…Thus, rather than being connected through, for example, follower/followee networks or through formal organizations, users of the hashtag come together through "ambient affiliation" (Zappavigna, 2011), that is, by bonding around the evolving topics of interest that are rendered findable by emerging hashtags. The hashtags that are created in relation to terror attacks are a way for individuals and collectives to share and discuss these events, and thus the hashtags function as a space for meaning-making practices (Eriksson, 2016).…”
Section: Previous Researchmentioning
confidence: 99%
“…However, situation assessment, sense-making and achieving SA based on social media content might differ from how these processes function in traditional media. Social media to a much larger degree represent alternative framings and counter-discourses on how to assess and understand a crisis (Eriksson, 2016;Lindgren, 2011). Especially micro-blogging services such as Twitter have proven to be 'privileged as platforms for backchannel activity' (McNely, 2009, p. 297), in which the dominant discourses of mainstream media can be countered and sense-making negotiated.…”
Section: Twitter and Situation Awareness Of Crisis Eventsmentioning
confidence: 99%
“…way of understanding and reacting to the terrible event and went hand-inhand with the dominant discourse found in the mainstream media (Kverndokk, 2013). In her hashtag specific analysis of the Twitter-sphere during the six days following the 22 July 2011 attack, Eriksson (2016) found that Twitter served as a backchannel for discourses countering the discourses of the mainstream media. These counter-discourses focused on 'vocabularies used to explain the attacks as well as the sensationalisation of the event' (Eriksson, 2016, p. 13).…”
mentioning
confidence: 99%